Determinant Factors Associated with the Implementation of Normal Childbirth Care (APN) in the Covid 19 Pandemic Era at Health Centers in Manado City - Chabibah, Ike F.A; Priska, Priska; Helly, Helly (Jurnal EduHealth, 2022)
Midwives as providers of professional midwifery services to women throughout their life cycle independently, collaboratively and/or referrals are one of the front lines in handling Covid 19, (IBI 2020). Maternal and neonatal mortality rates in Indonesia were still a big challenge in the pre-covid era, with the non-natural disasters spreading the 2019 Disease virus, it was feared that it would further increase the morbidity and mortality of mothers and newborns due to the reluctance of pregnant women to go to the puskesmas, (Directorate of Family Health 2020). The purpose of this study was to identify factors related to the implementation of normal delivery care (APN) in the era of the Covid-19 pandemic. The research method used a questionnaire for midwives throughout the city of Manado which would be processed using the Chi-square statistical test on 121 respondents as a population. The targeted output is in the form of publications in national journals accredited grades 1-6 and additional outputs in the form of copyrights (HAKI). TKT level in this study is 3.